Legal Protection for Consumers in Sales and Purchase Agreements Through the Cash on Delivery System - Hanna Novitasari, Lutfia; Mashadurohatun, Anis (TABELLIUS: Journal of Law, 2025)
The development of information technology has made it easier for people to carry out activities, such as buying and selling transactions. Buying and selling transactions can be conducted online between sellers and buyers, using a cash-on-delivery payment system. However, these transactions often result in defaults by the parties, necessitating legal protection for the injured party. Therefore, the purpose of this study is to determine and analyze the legal status of electronic cash-on-delivery sales and purchase agreements, as well as the legal protection for the parties in electronic cash-on-delivery sales and purchase agreements. This study uses a qualitative approach, focusing on in-depth observation. The results of this study indicate that legal protection for consumers in cash-on-delivery sales and purchase agreements is provided preventively by forcing the parties involved to fulfill their respective obligations. Meanwhile, repressive legal protection can be provided by parties by filing lawsuits against the party causing the loss through litigation or non-litigation channels. In practice, legal protection for consumers still poses various problems. These problems are influenced by various factors related to legal structure, legal substance, legal culture, and bureaucratic apparatus. In addition, the aim of legal protection for consumers is regulated in Article 3 of the Consumer Protection Law so that consumers can be safe and comfortable when making transactions.